2016
DOI: 10.1111/jeb.12932
|View full text |Cite
|
Sign up to set email alerts
|

Otolith shape lends support to the sensory drive hypothesis in rockfishes

Abstract: The sensory drive hypothesis proposes that environmental factors affect both signalling dynamics and the evolution of signals and receivers. Sound detection and equilibrium in marine fishes are senses dependent on the sagittae otoliths, whose morphological variability appears intrinsically linked to the environment. The aim of this study was to understand if and which environmental factors could be conditioning the evolution of this sensory structure, therefore lending support to the sensory drive hypothesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 86 publications
(157 reference statements)
1
36
0
Order By: Relevance
“…In conclusion, we have demonstrated that shape contours of gobiid otoliths can be used to automaticate identification of specimens to genus and even species. Moreover, we have detected an apparent phylogenetic clustering in the distinctive otolith patterns of the different lineages, as occurs in other fishes (Sadighzadeh et al, 2014), such shape patterns can help with understanding the evolution of the group (Tuset et al, 2016). This study were financed by projects "AFORO3D" (Ref.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…In conclusion, we have demonstrated that shape contours of gobiid otoliths can be used to automaticate identification of specimens to genus and even species. Moreover, we have detected an apparent phylogenetic clustering in the distinctive otolith patterns of the different lineages, as occurs in other fishes (Sadighzadeh et al, 2014), such shape patterns can help with understanding the evolution of the group (Tuset et al, 2016). This study were financed by projects "AFORO3D" (Ref.…”
Section: Discussionmentioning
confidence: 82%
“…Tuset et al . () used otolith shape to correctly identify 58.1% of 42 rockfish species (Sebastidae) and Sadighzadeh et al . () used otolith shape to correctly identify 65.5% of 12 snapper species (Lutjanidae).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on the ecomorphology and functional morphology of inner ear components should complement each other. Combined data sets including ecological, eco‐acoustical, life‐history, morphological (otoliths) and physiological (auditory) traits, in combination with phylogenetic information (Wainwright et al, ; Tsuboi, Gonzalez‐Voyer & Kolm, ; Tuset et al, ), would allow deeper insights into the potential selective forces affecting otolith morphology, including potential co‐evolution between (or developmental interdependencies of) otolith morphology and other inner ear components, as well as phylogenetic constraints on otolith evolvability. For example, Tuset et al .…”
Section: Evolution Of Teleost Otolithsmentioning
confidence: 99%